Left Out in the Academic Field: Doctoral Graduates Deal with a Decade of Disappearing Jobs - Acker, Sandra; Haque, Eve (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur)

(untitled) (Canadian Society for the Study of Higher Education, 2017)
In 2001–2002, the authors of this article interviewed 31 ethno-culturally diverse doctoral students about their experiences in a sociology of education program at a Canadian university. Approximately 10 years later, in a second qualitative study, we had the chance to conduct semi-structured interviews with 13 of the former students to find out what had happened to them in the intervening years. Two of the 13 had become tenured academics, three were on the tenure track after years in temporary positions, and most of the others worked in the contingent sector of the academic labour market. Bourdieu’s concepts of “habitus” and “field” are particularly useful for our analysis, and we explore the tensions between these concepts for our participants.